"Inaccessible environment": on the Issue of Inclusive pupils' education of a correctional type's orphanage" - Trubnikova N. V. (Socio-Pedagogical Issues of Education and Upbringing, 2025)
The article is devoted to the problems of obtaining quality education for children with disabilities - pupils of orphanages, an attempt was made to outline the need to return remedial classes to general education schools, taking into account the preservation of inclusion in extracurricular activities and additional educational programs.
Keywords: интеграция; integration; инклюзивная среда; тьютор; tutor; адаптивная программа; inclusive environment; adaptive program